Впровадження статистичних показників до методики аналізу ефективності грошових потоків підприємств - Роганова, Ганна Олександрівна (My University, 2019)
Проведено аналіз класичних методів оцінки ефективності управління грошовими потоками підприємств. Визначено характеристики статистичних показників грошових потоків на етапі аналізу ефективності управління ними. У процесі їхньої реалізації запропоновано підвищити якість оцінки за рахунок впровадження показників статистичного аналізу. Завдяки цьому забезпечується отримання якісної та всебічної оцінки синхронності формування (витрачання) грошових потоків у часі. The contemporary methods of corporate cash flow analysis are the object of this study. One of the most problematic points is how to provide proper cash flow analysis on a formation simultaneity basis over the time. The classical methods of corporate cash flow management efficiency analysis are considered and the basic parameters of its indicators are determined during the study. Unstable operating conditions of domestic companies, as well as existing inconsistency of the corporate reporting with International Financial Reporting Standards make it difficult to generate timely and adequate information about cash flows of a company. The main phases of cash flow management effectiveness analysis are defined herein. They include collecting and processing the data, identifying the factors and risks, analyzing the cash flows of the previous period, determining the financial resources and cash needs, budgeting the investments and monitoring the cash flows. Throughout this study, it is proposed to improve the quality of cash flow analysis by introducing certain statistical cash flow analysis indicators. Due to this, it is possible to obtain a high-quality and comprehensive assessment of the formation simultaneity and expenditure of cash flows over the time. The drawbacks of the classical (horizontal, vertical, comparative and ratio) methods of analysis are also described herein. Thus, certain classical statistical indicators are proposed to apply while evaluating the cash flows. Compared to other classical methods, statistical analysis has certain advantages as it allows to identify the relationships between cash flows, closeness of such relationships and their volatility, thereby making the mechanism for evaluating cash flows more holistic.
Keywords: статистика; метод; аналіз; ефективність управління; грошові потоки; statistics; method; analysis; management efficiency; cash flows; фінанси; finances; кафедра фінансів